PERBANYAKAN Heritiera javanica (Blume) Koesterm. SEBAGAI JENIS PENGHASIL KAYU PADA BERBAGAI INTENSITAS NAUNGAN DAN MEDIA PERTUMBUHAN - Sahromi Sahromi; R. Subekti Purwantoro; Hartutiningsih M. Siregar (BERITA BIOLOGI, 2015)
Heritiera javanica is a timber tree species and their natural regeneration is scanty, thus propagation of this species is urgently required. This research was aimed to identify the effect of shade intensity and growth media on the survival rate and growth of seedlings. Experi- mental design used was completely randomized with two factors, namely the shade intensity and the media that consisted of several cate- gories. Parameters measured were survival rate and seedlings growth; height, number of leaves, and number of roots. Survival rate was analyzed using descriptive statistics. Seedlings growth (height, number of leaves, and number of roots) were estimated by using analysis of variance. Results showed that treatments using categories of several media categories that were placed in the shade of 25%, 50%, and 85% had a high survival rate. In addition, seedlings that were placed in 50% shade grew better and optimally. Media of TK (soil + compost), TS (soil + chaff), and TSPk (soil + manure + chaff) that were placed on the 50% shade showed the best result to height of seedlings growth. Reintroduction needs to be done for the enrichment of H. javanica populations in nature.